DIGITALISASI MANAJEMEN PERSEDIAAN UMKM MELALUI IMPLEMENTASI ERP ODOO PADA SESERAHAN HANALUNA PEMALANG - Riza, Laeli Atikha; Poerwati, Tjahjaning; Hardiningsih, Pancawati (Intimas, 2026)
Inventory management is a crucial aspect in ensuring the smooth operation of business activities, yet many micro, small, and medium enterprises (MSMEs) still rely on manual recording systems that are prone to errors and inefficiencies. Enterprise Resource Planning (ERP) systems such as Odoo provide an integrated platform to automate the recording, monitoring, and reporting of inventory transactions in real-time. This community service project was conducted at Seserahan Hanaluna, an MSME in Pemalang, through a blended learning method combining face-to-face workshops and online tutorials. The training emphasized experiential and case-based learning, enabling participants to practice directly on Odoo’s inventory and accounting modules. The results show that Odoo significantly improves inventory transparency by providing real-time stock data, valuation reports, and automatically integrated financial statements. Furthermore, the training enhanced participants’ understanding of ERP concepts and increased their technical skills in operating the system. The adoption of Odoo not only streamlines inventory recording but also strengthens internal control, improves decision-making reliability, and raises awareness of the importance of digitalization for MSME sustainability.